2008
DOI: 10.1007/s10388-007-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of tracheomediastinal fistula after tracheal injury obtained during esophagectomy using the pectoralis major muscle: a case report

Abstract: When tracheal injury occurs during esophagectomy, it is a very serious and frequently fatal complication. We experienced a case of intractable tracheomediastinal fi stula caused by tracheal injury during esophagectomy that was successfully repaired using a pedicle fl ap of the left pectoralis major muscle. A 55-year-old Japanese man who had congenital right aortic arch was referred to our hospital with a complaint of dysphagia. He had a type 2 carcinoma from the distal part of the cervical esophagus to the upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…There are reports of attempts to repair these conditions directly by suturing and covering with omentum or muscle flap. Such an operation was thought to be necessary if the fistula leads to a respiratory tract because repetitive pneumonia would result in a poor physical condition [3,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are reports of attempts to repair these conditions directly by suturing and covering with omentum or muscle flap. Such an operation was thought to be necessary if the fistula leads to a respiratory tract because repetitive pneumonia would result in a poor physical condition [3,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the few cases in which it is impossible to accomplish primary closure require an esophageal bypass or esophagectomy and meticulous planning including nutritional management. There are also reports of the use of a muscle flap in the pectoralis major to repair a tracheo-mediastinal fistula after esophagectomy [3]. These surgical operations are invasive, and we decided instead to perform endoscopic clipping and filling with fibrin glue to treat an esophago-mediastinal fistula.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…When the abscess was limited to the pleural cavity, a chest tube could achieve adequate drainage. However previous studies had revealed that most of the contained leaks were limited to the mediastinum [4,5]. It is difficult to deal with this type of leakage because abscess cavities close to the mediastinum are difficult to reach with a conventional chest tube.…”
Section: Conservative Managementmentioning
confidence: 99%
“…Conservative treatment with nutritional support and antibiotic therapy is usually adopted at first, but this is sometimes insufficient to obliterate leakage or can take 20-30 days, even if it is successful. Anastomotic leakage is usually improved simply by draining the anastomotic site [3], but sometimes an esophago-respiratory fistula occurs due to penetration by the abscess to the trachea or main bronchus [4][5][6]. This causes a very serious clinical condition, predisposing the patient to life-threatening pneumonia.…”
Section: Introductionmentioning
confidence: 99%